Polymer photonic sensing skin - Kalli, Kyriacos; Zhang, Chi; Webb, David J.; Van Hoe, Bram; Van Steenberge, Geert; Chen, Xianfeng; Berghmans, Francis; Thienpont, Hugo; Urbanczyk, Waclaw; Sugden, Kate; Peng, Gangding (My University, 2010)
A highly flexible sensing skin with embedded polymer optical fibre Bragg gratings is characterised The response to pressure and strain compare favourably to a similar skin instrumented with silica fibre Bragg grating sensors.
Keywords: Silica; Fibers; Bragg gratings; Fiber optics; Optical fibers